Backward-propagating source as a component of rising tone whistler-mode chorus generation - Harid, Vijay; Gołkowski, Mark; Hosseini, Poorya; Kim, Hoyoung (Frontiers in Astronomy and Space Sciences, 2022)
Whistler mode chorus waves in the magnetosphere play a crucial role in space weather via wave-particle interactions. The past two decades have observed tremendous advances in theory and simulations of chorus generation, however, several details of the generation mechanism are still actively contended. To simulate chorus generation, a new envelope particle-in-cell code is introduced. The model produces a rising tone chorus element in a parabolic geomagnetic field. The initial chorus element “embryo” frequency is shown to initialize near the equator at the frequency of maximum linear growth. A backward resonant current is then observed to propagate upstream of the equator. The trajectory of the backward current follows that of a freely falling electron that has been de-trapped at the equator superimposed with forward motion at the group velocity. The backward current iteratively radiates a rising tone element where the highest frequency components are generated furthest upstream. The work provides new advancements in modeling chorus and corroborates other recent work that has also demonstrated a backward-moving source during the generation of coherent whistler mode waves.